Changing patterns of motor vehicle collision risk during winter storms: A new look at a pervasive problem. (June 2019) - Mills, Brian; Andrey, Jean; Doberstein, Brent; Doherty, Sean; Yessis, Jennifer
Highlights: A new approach was used to estimate the risks of injury and non-injury collisions during winter storms. Injury and non-injury collisions increased by 66 and 137 percent, respectively, during winter storms. Risks declined significantly from 2002 to 2016. Driver behavior and road maintenance practices may explain variation in risk across storm types. Abstract: Past research has shown that winter precipitation is an important environmental factor that increases the frequency of motor vehicle collisions that cause personal injury and property damage. Questions remain about the magnitude of winter storm effects on collision occurrence, changes in risk over time, and the role of driver behaviour in conjunction with other factors (e.g., winter maintenance by road authorities) as it affects exposure and sensitivity to hazardous conditions. In response, a matched-pair, retrospective cohort method was used to estimate injury and non-injury collision risks for a mid-sized urban community based on a new definition of winter storm events that, relative to previous studies, captures a greater portion of time during which drivers respond to hazardous weather and road surface conditions. Winter storm definition criteria were applied to weather radar imagery and traditional surface station observations in a unique manner to classify and characterize a set of 196 variable-length storm events in terms of precipitation type and amount, visibility, temperature profile, presence of government-issued warnings, location, and temporal factors. Injury and non-injury collisions increased by 66 and 137 percent, respectively, during winter storms relative to dry weather conditions. Although these increases were higher than findings from similar studies of winter precipitation events conducted over the same timeframe (i.e., 2002–2016), they were found to have declined by a statistically significant amount over the course of the study period and disproportionately to collisions in general. Understanding why this is occurring, and then attributing improvements to specific winter road safety interventions and behavioural adjustments, is a key focus for future research and for informing future risk-mitigating investments.